2018
DOI: 10.1007/978-3-030-02131-3_32
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Media on Entrepreneur Motivation and Marketing Strategies in a Developing Country

Abstract: Entrepreneurs are increasingly using social media in running their businesses. This phenomenon is remarkable especially in developing countries where entrepreneurs now exploit business opportunities by using cheaper platforms. Prior studies claim that social media plays a crucial role in establishing a business and ensuring its survival through effective marketing. However, from the context of developing countries, limited research has sought to understand the role of social media in motivating entrepreneurs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The above research results show that the popularity of entrepreneurs and online interaction behaviors do have a significant impact on public feedback. These findings are consistent with research conducted by other academics (Briley and Aaker, 2006;Albert et al, 2017;Olanrewaju et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The above research results show that the popularity of entrepreneurs and online interaction behaviors do have a significant impact on public feedback. These findings are consistent with research conducted by other academics (Briley and Aaker, 2006;Albert et al, 2017;Olanrewaju et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…), entrepreneurs' online interactive information is easier to retain and trace back, and thus easier for consumers to obtain, enabling them to directly respond to, participate in, and interact with this information (Girginova, 2013). Therefore, the online interactive information of entrepreneurs serves as an important clue for the public to evaluate entrepreneurs and affects the image of entrepreneurs in the minds of the public (Olanrewaju et al, 2018).…”
Section: Entrepreneurs' Online Interactive Behavior and Investor Feed...mentioning
confidence: 99%
“…The usage of dummy variables also could worsen the results, because the clustering is ideally based on non-binary variables. As a future research direction, the characterization of the farms' leaders could be given because many articles have studied the relation between the leaders' character and the applied marketing strategy [53,54,63,64]. However, a comprehensive analysis of farm leaders has not yet been published.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the link between social media use and drivers of entrepreneurship is scarce, one of the few investigations was published by Olanrewaju et al (2018), who explored how social media influences Nigerian entrepreneurs' motivation to start a business and found that most entrepreneurs were driven by opportunity rather than necessity due to the opportunities offered by social media. As it was argued, frequent exposure to family, social, political, and ecological content on social media sites such as Twitter, Facebook, Instagram, and LinkedIn should imply different perceptions of entrepreneurship and sustainability, and in this line, this research proposes that such discrepancies should also be expressed in the students' perceptions of the drivers of entrepreneurship.…”
Section: Drive For Entrepreneurshipmentioning
confidence: 99%